A Comparison of Hypnotic Induction, Task Motivation, and a "Cold Start" Control Group on Hypnotizability. Issue 2 (14th October 2016) - Krystek, Stephen; Kumar, V. K.
Abstract : Groups of participants ( N = 164) were randomly assigned to three conditions: Group 1 received a trance induction, Group 2 received task-motivational instructions, and Group 3—"cold start" control—was simply told, "We will begin the hypnosis procedure now." All participants received the Creative Imagination Scale suggestions and then completed the Creative Imagination Scale and Inventory Scale of Hypnotic Depth. The three conditions did not differ significantly either on the Creative Imagination Scale or in reported hypnotic depth. These results are consistent with prior studies which show that trance induction and task-motivational yield similar results, but they are inconsistent inasmuch as the trance induction and task-motivational groups did not differ from the control group. These results, however, are predictable from socio-cognitive perspectives that the context of hypnosis itself can elicit hypnotic behaviors.